PELATIHAN FOTOGRAFI PRODUK GUNA MENINGKATKAN OPTIMALISASI DIGITAL MARKETING PRODUK UMKM - Erna Susanti; Fitri Firdalius; Maharian Agung (LPPM Universitas Bina Bangsa, 2024)
In the internet media era, caused affects various sectors, including the economic sector. This can be seen from promotional activities, marketing, and financial transactions using the internet. The wide market that can be reached by promotional and sales activities using the internet, which is currently known as Digital Marketing, requires the MSME sector to be more creative and innovative in using internet media and designing promotional designs for their products, in this case visual designs in the form of photos. Photos product that are quite interesting and creative. Photos product or commercial photos are all images of a product that will be sold. To produce quality product photos you need a quality camera, both a professional camera and a smartphone camera. Currently, smartphones offer attractive features with quality hardware. The method that will be used in this PKM activity is the training and mentoring method. The training material includes digital marketing tutoring and photography exercise by smartphones. The form of assistance is producing good and quality product photos for use in online and offline promotions and marketing. With the implementation of this PKM, it is expected could assist to MSMEs improve their understanding of digital marketing comprehensively and able to produce quality product photos.